PENGARUH IKLIM ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT JURAGAN WIFI INDONESIA - Nurul Nada Fajrina; Sudiarto (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of organizational climate and work discipline on employee performance at PT Juragan Wifi Indonesia. The research uses a quantitative approach with primary and secondary data collected through survey methods and analyzed using multiple linear regression. The research results show that organizational climate and work discipline have a significant positive impact on employee performance, both partially and simultaneously. An improvement in these two variables is expected to optimally enhance employee performance, with management support to create a conducive work environment and consistent discipline standards.